2017
DOI: 10.1055/s-0037-1603890
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Perinatal Outcome of Nonimmune Hydrops Fetalis in Southern China

Abstract: Objective  This study aims to analyze the etiology and perinatal outcome of nonimmune hydrops fetalis (NIHF) in Southern China. Methods  All cases with NIHF diagnosed antenatally from January 1, 2007 to December 31, 2014 were identified and analyzed. Results  Total 482 cases of NIHF were identified during the study period. The most common cause of NIHF was hemoglobin (Hb) Bart's disease (61.8%), followed by chromosomal abnormalities (13.5%), idiopathic etiology (13.1%), cardiac abnormalities (6.4%), and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Hb Bart's disease or homozygous alpha 0 -thalassemia remains the most prevalent cause of fetal anemia in northern Thailand, indicating a high gene frequency of alpha 0 -thalassemia in the population. The leading diagnosis of Hb Bart's disease in our study is consistent with that reported in previous studies in Thailand and China (2,7,13,15). Increasingly, diagnosed causes of fetal anemia are non-deletional alpha-thalassemia and hereditary Fetal anemia in northern Thailand red cell membrane disorders.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hb Bart's disease or homozygous alpha 0 -thalassemia remains the most prevalent cause of fetal anemia in northern Thailand, indicating a high gene frequency of alpha 0 -thalassemia in the population. The leading diagnosis of Hb Bart's disease in our study is consistent with that reported in previous studies in Thailand and China (2,7,13,15). Increasingly, diagnosed causes of fetal anemia are non-deletional alpha-thalassemia and hereditary Fetal anemia in northern Thailand red cell membrane disorders.…”
Section: Discussionsupporting
confidence: 91%
“…negative blood group (1.7%) compared with that in Western populations (17.3%) (5). The leading cause of fetal anemia among Asian populations is hemoglobin (Hb) Bart's disease resulting from homozygous alpha 0 -thalassemia (2,(6)(7)(8).…”
Section: Original Articlementioning
confidence: 99%
“…Published data suggest that rates of legal termination may be high following detection of NIHF during pregnancy. In the recent study by He et al, 26 459 (95.2%) out of 482 cases of NIHF detected by ultrasonography during pregnancy ended in spontaneous or legal termination, with only 23 (4.8%) cases continuing to birth. Thus, legal terminations and late miscarriages may contribute to the lower incidence reported here compared with other studies.…”
Section: Discussionmentioning
confidence: 93%
“…7 The prognosis of the fetus depends on the cause of NIHF and gestational age; perinatal mortality ranges from 55%-98%. [8][9][10] Moreover, identifying the underlying etiology of NIHF is important for managing both the current pregnancy and determining the recurrence risk for future pregnancies.…”
Section: Introductionmentioning
confidence: 99%